2015
DOI: 10.1007/s00604-015-1585-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotubes doped with boron as an electrode material for electrochemical studies on dopamine, uric acid, and ascorbic acid

Abstract: Boron-doped multi-walled carbon nanotubes (B-MWCNTs) were deposited on oxidized silicon substrate via decomposition of ethanol and boric acid in the presence of the catalyst ferrocene by means of chemical vapor deposition in a thickness of typically 900 nm. The B-MWCNTs were characterized using Raman spectroscopy and scanning electron microscopy and transmission electron microscopy in combination with energy dispersive X-ray spectroscopy. The deposited BMWCNTs were electrochemically characterized using the fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Developing HPOM-based materials in EC-sensing and biosensor applications has been acknowledged as one of the most promising potentials in POM chemistry, owing to the ideal reversible charge-transfer capability of HPOMs. Studies have demonstrated that HPOMs can act as efficient electron donors or acceptors without structural change, which makes HPOMs valuable candidates for electron-exchange reactions. Because of their unique electronic structure, CNs have been favorably investigated to prepare POM–CN composites, in which a combination of POMs and CNs will contribute to a significantly enhanced electronic transport capability . Considering all of the above-mentioned factors, the composite of 1 with CFMCN has been proposed to modify glassy carbon electrodes (GCEDs) for further the EC detection of EDO.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Developing HPOM-based materials in EC-sensing and biosensor applications has been acknowledged as one of the most promising potentials in POM chemistry, owing to the ideal reversible charge-transfer capability of HPOMs. Studies have demonstrated that HPOMs can act as efficient electron donors or acceptors without structural change, which makes HPOMs valuable candidates for electron-exchange reactions. Because of their unique electronic structure, CNs have been favorably investigated to prepare POM–CN composites, in which a combination of POMs and CNs will contribute to a significantly enhanced electronic transport capability . Considering all of the above-mentioned factors, the composite of 1 with CFMCN has been proposed to modify glassy carbon electrodes (GCEDs) for further the EC detection of EDO.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Boron doped (B‐MWCNTs) grown on oxidized silicon substrate by chemical vapor deposition gave the response towards DA, UA, AA oxidation. The LOD for these three procedures was found to be 0.11, 0.65, and 1.21 μM respectively …”
Section: Electrochemical Sensing Of Da By Using Cnt‐based Materialsmentioning
confidence: 97%
“…The LOD for these three procedures was found to be 0.11, 0.65, and 1.21 μM respectively. [58] A novel electro spun polyamide 6/poly(allylamine hydrochloride) (PA6/PAH) nanofibers-MWCNT DA sensor determined the linear response from 1 to 70 μM with LOD 0.15 μM. [59] MWCNT modified GCE with various functional groups, such as carboxyl containing MWCNT (MWCNT/COOH/ GCE), acid treated MWCNT (MWCNT/T/GCE), hydroxyl containing MWCNT (MWCNT/OH/GCE), pristine MWCNT (MWCNT/P/ GCE), were prepared and tested for DA, UA and AA electrocatalytic oxidation.…”
Section: Cnts Directly Deposited/grown On Electrodes or Functionalizementioning
confidence: 99%
“…Tsierkezos et al reported the simultaneous detection of dopamine, UA, and AA by modifying a GCE with boron-doped MWCNTs (B-MWCNTs). This sensor exhibited dopamine, UA, and AA detection at working potentials of ∼0.267, ∼ 0.412, and ∼0.127 V with LODs of 0.11, 0.65, and 1.21 μM, respectively …”
Section: Overview Of Carbon-based Voltammetric Biosensorsmentioning
confidence: 99%
“…172 This sensor exhibited a wide linear response for AA and dopamine over the concentration range of 1 × 10 −7 to 9 × 10 −6 M and 1 × 10 −7 to 8 × 10 −6 M with LODs of 0.07 and 0.08 μM, respectively. 173 A multielectrode array (MEA) dopamine sensing chip has been created by electroplating CNTs onto an indium−tin oxide MEA. 77 This sensor was used to sense dopamine (LOD, 1 nM) release from mouse striatal brain slices (coronal and sagittal slices), and these results corresponded with the expected results found in other studies using carbon fiber electrodes (Figure 4).…”
Section: Overview Of Carbon-based Voltammetric Biosensorsmentioning
confidence: 99%